The management of English as medium of instruction (EMI) policy at an Indonesian technological institution - Erliana, Santi; Cahyono, Bambang Yudi; Widiati, Utami; Basthomi, Yazid (Universitas Islam Negeri Palangka Raya, Indonesia, 2024)
Due to its internationalization agenda, higher education institutions (HEI) in Indonesia adopted English as medium of instruction (EMI) programs despite the absence of a national policy document to regulate EMI. Studies on EMI policy in HEI focused on the effect policy could have on the dominant group and gave less highlight on EMI policy implementation management. This case study examined the management of EMI as language policy at the meso-(institutional) and micro-(classroom) levels. The data sources include the institutional policy document related to the EMI program, and interviews with seven EMI officers and seven EMI teachers at a Technological Institute in Indonesia. Using Spolsky's language management framework for the